2016
DOI: 10.14238/sp11.3.2009.167-73
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Proteksi Air Susu Ibu Terhadap Infeksi

Abstract: A ir susu ibu (ASI) sangat diperlukan selama masa pertumbuhan dan perkembangan bayi.1 Selain mengandung zat nutrisi yang dibutuhkan, ASI juga meningkatkan daya tahan dan mengandung anti bakteri dan anti virus yang melindungi bayi terhadap infeksi. 2,3 Dalam laporan WHO disebutkan bahwa hampir 90% kematian balita terjadi di negara berkembang dan lebih dari 40% kematian disebabkan diare dan infeksi saluran pernapasan akut, yang dapat dicegah dengan ASI eksklusif. 2,4Tahapan sekresi ASI diawali dengan pengeluaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
7
0
5
Order By: Relevance
“…10 The secretory IgA itself has been proven to have an in vitro antibacterial effect against Streptococcus pyogenes. 11 The non-specific protective factors may also contribute to the antibacterial effect of human milk. Lactoferrin, a protein in human milk can demonstrate a bacteriostatic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The secretory IgA itself has been proven to have an in vitro antibacterial effect against Streptococcus pyogenes. 11 The non-specific protective factors may also contribute to the antibacterial effect of human milk. Lactoferrin, a protein in human milk can demonstrate a bacteriostatic effect.…”
Section: Discussionmentioning
confidence: 99%
“…10 All of the non-specific factors have shown in vitro activity against common pathogens like Staphylococcus aureus, Escherichia coli, Vibrio cholera and Haemophilus influenzae. 11 A previous study using probiotic of the human milk has shown that there is an antibacterial activity against common pediatric communityacquired respiratory pathogens. The probiotic of the human milk can inhibit the growth of Streptococcus pneumonia, Haemophilus influenzae and Staphylococcus aureus tested in this study, 13 thus, confirming that the human There is another study reporting the exclusively breastfed infants who have less hospitalization caused by respiratory tract illness compared to non-breastfed infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini dapat dicegah dengan ASI eksklusif. [2][3][4] Data dari National Immunization Survey di Amerika pada tahun 2004, 70,3% ibu pernah menyusui, 36,2% ibu melanjutkan sampai bulan ke-6, 38,5% ibu menyusui eksklusif sampai bulan ke-3, dan 14,1% ibu menyusui eksklusif sampai bulan ke-6. Diare dan infeksi saluran nafas sampai saat ini masih menjadi masalah kesehatan masyarakat di dunia, terutama negara berkembang termasuk Indonesia, dan merupakan salah satu penyebab morbiditas dan mortalitas tertinggi pada anak usia balita.…”
unclassified
“…Lisozim juga merupakan salah satu faktor yang dapat memengaruhi mikroflora usus bayi. 2,8 Lisozim dalam satuan volume yang sama pada ASI mengandung 300 kali lebih banyak dibandingkan susu sapi. Aktivitas antimikroba lisozim yang terdapat dalam cairan tubuh telah dibuktikan secara in vitro.…”
unclassified